Strategi Survival Masyarakat Pesisir dan Pedalaman Sumenep di Tengah Krisis Ekologi dan Industrialisasi - Shohebul Umam (LP2M of Institute for Research and Community Services - UIN Walisongo, 2020)
This study discusses poverty, which until now is still a major problem for the Indonesian state. The effort to eradicate poverty becomes a big commitment through the projected Sustainable Development Goal's (SDG's) which are determined to reduce the number of poor people to 50% in the next 2030. Instead of alleviating poverty, SDG's which insinuate welfare are more and more pressed by poverty itself. Global warming which drives climate change is uncertain, causes an ecological crisis on one side, and creates a consumptive culture of society on the other side. This research uses a qualitative method, in which coastal communities and inland farmers become in Sumenep, Madura is the object of this study. due to climate change that is getting worse, fishermen and farmers, must rearrange their survival strategies to meet the needs of family income. The government, in this case, must be encouraged to be a catalyst for change, in order to realize the social welfare of the community through the development of community-based communities that are independent and sustainable. Penelitian ini membahas tentang kemiskinan, yang sampai saat ini masih menjadi persoalan utama negara Indonesia. Upaya untuk mengentaskan kemiskinan menjadi komitmen besar melalui proyeksi Sustainable Development Goal’s (SDG’s) yang bertekad untuk menekan jumlah penduduk miskin hingga 50% pada 2030 mendatang. Alih-alih mengentaskan kemiskinan, SDG’s yang meng-insinuasikan kesejahteraan justru samakan terdesak oleh kemiskinan itu sendiri. Global warming yang mendorong perubahan iklim tidak menentu, menyebabkan krisis ekologi pada satu sisi, dan menciptakan budaya konsumtif masyarakat pada sisi yang lainnya. Penelitian ini menggunakan metode kualitatif, di mana masyarakat pesisir dan petani pedalaman menjadi di Sumenep, Madura menjadi objek kajian ini. akibat perubahan iklim yang semakin buruk, nelayan dan petani, harus mengatur kembali strategi survival mereka untuk memenuhi kebutuhan nafkah keluarga. Pemerintah dalam hal ini, mesti didorong untuk menjadi katalisator perubahan, demi mewujudkan kesejahteraan sosial masyarakat melalui pengembangan masyarakat berbasis komunitas yang bersifat mandiri dan berkelanjutan.